Analisis Governance Networks Dalam Implementasi Sanksi Diskualifikasi Peserta Pilkada Di Indonesia - Muhammad Haekal Saniarjuna; Rachma Fitriati (Kolaborasi : Jurnal Administrasi Publik, 2023)
This article discusses implementing the disqualification policy for election participants in Indonesia, which involves two institutions, namely the Election Supervisory Body (Bawaslu) and the General Elections Commission (KPU). This article raises the issue of the relationship between Bawaslu and KPU in implementing disqualification sanctions for participants in the 2020 Regional Head Elections (Pilkada) in Indonesia, where there were seven recommendations for Bawaslu disqualification that the KPU should have. The author uses a qualitative approach with a literature review research method and uses secondary data. The research results in this article show that the governance network between Bawaslu and KPU in implementing disqualification sanctions for Pilkada participants does not work equally because they need clear rules. The relationship that has been developed shows that the KPU has a higher position than the Bawaslu because it can only accept or follow up on the Bawaslu's disqualification recommendations. Furthermore, the rules regarding the disqualification of Pilkada participants, as stipulated in Law Number 10 of 2016, do not stipulate the KPU's obligation to implement the Bawaslu recommendation. This condition caused the implementation of the disqualification of Pilkada participants in Indonesia not to go well because many Pilkada participants who have been proven to have committed fraud did not receive any sanctions.